Globalization, poverty and inequality: What is the relationship? What can be done? - Kaushik Basu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
The paper studies the relation between globalization, inequality and marginalization, within and across nations. It reviews the existing evidence on globalization and global inequality and argues, using a simple theoretical model, that the two are inter-connected. It discusses policy alternative policies to counter extreme poverty and inequality. The paper takes the view that curbing these, even within one country, requires global, cross-country policies that we do not currently have, and advocates the setting up of an international initiative to coordinate such policies. – globalization ; inequality ; international organization ; poverty
Keywords: I30; O15; O19; F42; 330; Globalisierung; Einkommensverteilung; Armut; Entwicklungsländer